The dam keeper. Book 2, World without darkness - Kondo, Robert; Hashizume, Yohei; Song, JJ Jaehee; Vongsayan, Kitikhun Pan; Tsutsumi, Daisuke, 1974- (New York, New York : First Second, 2018)
Beyond the dam lies certain death -- this is something every citizen of Sunrise Valley knows well. Yet when a poisonous black tidal wave carries Pig, Fox, and Hippo over the dam and into the wastelands, they don't find death. Instead they find bustling cities, each with a dam of its own. But who is the unknown dam keep behind it all? As Pig is drawn deeper into the mystery, another danger is brewing. In just eight days, the wave of deadly black fog will return to the east. A world beyond his imagining lies between him and his home.
Based on the motion picture The dam keeper.
School Library Journal, July 2018
3.4
3-6
GN530L
Keywords: Dams -- Comic books, strips, etc. -- Juvenile fiction; Fear -- Comic books, strips, etc. -- Juvenile fiction; Orphans -- Comic books, strips, etc. -- Juvenile fiction; Fathers and sons -- Comic books, strips, etc. -- Juvenile fiction; Dams -- Fiction; Fear -- Fiction; Orphans -- Fiction; Fathers and sons -- Fiction; Comics adaptations